2022
DOI: 10.3390/jcdd9120444
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Septal Versus Apical Pacing: Long-Term Incidence of Heart Failure and Survival

Abstract: The clinical benefits of right ventricular septal (RVS) pacing compared to those of right ventricular apical (RVA) pacing are still in debate. We aimed to compare the incidence of heart failure (HF) and all-cause mortality in patients submitted to RVS and RVA pacing during a longer follow-up. This a single-center, retrospective study analysis of consecutive patients submitted to pacemaker implantation. The primary outcome was defined as the occurrence of HF during follow-up. The secondary outcome was all-cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Moreover, the results of the SEPTAL-PM trial found no difference in LVEF, quality of life scores and functional status between RVS pacing and RVAP at 18 months [ 11 ]. Only one study has reported a higher risk of heart failure events with RVAP, however this study included high numbers of patients with co-morbidities known to be associated with heart failure events, such as baseline LV impairment and AF, when compared to other studies [ 12 ]. As a result of this, current guidelines do not recommend the preferential use of either RVAP or RVS pacing over the other.…”
Section: Pacemakers For Brady-arrhythmiasmentioning
confidence: 99%
“…Moreover, the results of the SEPTAL-PM trial found no difference in LVEF, quality of life scores and functional status between RVS pacing and RVAP at 18 months [ 11 ]. Only one study has reported a higher risk of heart failure events with RVAP, however this study included high numbers of patients with co-morbidities known to be associated with heart failure events, such as baseline LV impairment and AF, when compared to other studies [ 12 ]. As a result of this, current guidelines do not recommend the preferential use of either RVAP or RVS pacing over the other.…”
Section: Pacemakers For Brady-arrhythmiasmentioning
confidence: 99%